By understanding the problems of prohibition of abuse of labor rights - Сидоренко, А. С. (Theory and practice of jurisprudence, 2016)
This article discusses the problem of prohibition of abuse of labor rights. The legal nature of abuse of the right design is defined. It is noted that the principle of prohibition of abuse of the law is applicable in the context of the limits of law and of statutory safeguards